Political Leadership and Organizational Communication in the Film Tepatilah Janji: A Barthesian Semiotic Analysis - Suhaily Amri Hasibuan; Elfi Yanti Ritonga (Fakultas Ushuluddin Adab dan Dakwah UIN Sultanah Nahrasiyah Lhokseumawe, 2026)
This article analyzes how Tepatilah Janji (2024) represents organizational communication and political leadership within Indonesian party politics. The study is guided by two questions: how does the film construct party communication, leadership performance, and political promises as cinematic signs; and what myths of populist leadership are normalized through these signs. Methodologically, the research is positioned as qualitative film-text analysis using Roland Barthes’ semiotics, supported by a literature review on political communication, leadership, and Islamic communication ethics. The analysis maps selected scene units into signifier, signified, denotation, connotation, and myth, then interprets them through the ethical principles of shiddiq and al-wafa bi al-'ahd. The findings show that campaign performances, repeated diction such as rakyat, kesejahteraan, and pengabdian, and the visual contrast between elite political spaces and ordinary citizens construct a dramaturgy of leadership in which promises appear as moral commitments but operate as negotiable political commodities. Specifically, the film juxtaposes populist public speech with backstage elite bargaining, exposing a gap between political image and organizational integrity. This study affirms that semiotic analysis of broadcasting media is important for strengthening political literacy and criticizing the ethical crisis of party communication in contemporary Indonesia within Indonesia's evolving democratic and religious public sphere today.